PENGARUH KELOMPOK ACUAN DAN KELUARGA TERHADAPKEPUTUSAN PEMBELIAN BATIK TULIS JETIS PADA TOKOAMRI JAYA SIDOARJO - FITRIYAH, NIKMATUL (Jurnal Pendidikan Tata Niaga (JPTN), 2013)
From the test results showed that together the variables of the reference group and family proved to significantly influence purchasing decisions, and based on a partial test for independent variables in the form of reference group, (shown) has a positive and significant effect on purchasing decisions, and based on a partial test for independent variable in the form of family , (shown) has a positive and significant effect on purchasing decisions, while among two independent variables consisting of the reference group and family, was the most dominant influence on the effect of purchasing decisions is family. Keywords: reference groups, family, purchasing decisions